Health shocks and changes in preventive behaviors: Results from the China Health and Retirement Longitudinal Study - Zhang, Peng; Jiang, Hongli; Chen, Wen (Frontiers in Public Health, 2022)
Background: China is facing the challenge of rising prevalence and ballooning burden of chronic non-communicable diseases (NCDs), however, the Chinese middle- and older-aged population considerably lack preventive behaviors. Health shocks (HS), widely defined as sudden health deterioration brought on by diseases or accidents, bring a “teachable moment” to motivate changes in preventive behaviors. Objective: This study aimes to examine the effect of HS on changes in preventive behaviors including personal health practices and preventive care utilization. Methods: HS was defined as any five chronic disease diagnosis (cancer, heart disease, stroke, diabetes, and hypertension). The impacts of HS on smoking, drinking, and exercise, physical examination were estimated. The panel data of 13,705 respondents were obtained from the latest two waves of the China Health and Retirement Longitudinal Study (CHARLS) in 2015 and 2018. A multilevel propensity score match difference-in-difference (multilevel PSM-DID) model was constructed. Results: HS significantly decreased smoking (OR=0.59, p<0.05) and drinking (OR=0.62, p<0.01) and increased the utilization of auxiliary inspection in physical examination (OR=1.19, p<0.1). Major HS had significantly considerable and specific effects on reducing smoking and drinking (OR=0.37 and 0.56, p<0.01), while minor HS had relatively small effects on reducing smoking (OR=0.74, p<0.05) and drinking (OR=0.69, p<0.01) but extensive effects on initiating exercise (OR=1.32, p<0.05) and physical examination (OR=1.18, p<0.1) and auxiliary inspection (OR=1.30, p<0.05). Conclusion: After HS, there is a teachable moment to promote positive changes in preventive behaviors. Guided by the 5A’s brief intervention model (Ask, Advise, Assess, Assist, Arrange), tailored interventions should be targeted at these populations to reduce the risk of the progression and complications of existing diseases, prevent the related comorbidity, and prolong the expected life-span